Life Cycle Costs of Dutch school buildings. Issue 3 (19th August 2014) - de Jong, Peter; Arkesteijn, Monique; Cooke, Howard; Cooke, Howard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose There is a gap between the investment in and the operating costs of public school buildings, caused by the splitting up of responsibility for the financing of the accommodation. Municipalities finance the initial costs of construction, and school boards are responsible for the operating costs. According to architecture-based research on this subject this split-up results in higher costs during the lifetime of the buildings. This problem is often referred to as the split-incentive problem. This article aims at providing case-based evidence in order to support the idea that an integral approach using life cycle costs (LCC) would lead to more in-depth argued adjustments towards sustainable and feasible school buildings. Design/methodology/approach The research conducted nine case studies of newly-built secondary school buildings. The schools were examined with reference to building characteristics, building costs and operational costs. The sustainable performance of these cases is described with the aid of a Dutch sustainability measurement tool. The core of the research is the life cycle costs analysis and the overall perspective on the ratio between initial costs and operations costs. Findings It is often held in the construction sector that investments in sustainability lead to increased expense. However, studies indicate this is not unequivocally true. Our study, at least, found no clear evidence that schools with investments in specific sustainable solutions have such undesirable higher investment costs. Our study found some positive effects of sustainable measurements on the life cycle costs of secondary schools. Originality/value This study confirms the ratio of Hughes and Ive as defined in office typologies to be true in the school building typology. It is worthwhile for owners and users to keep focus on LCC, as well as for the government as financiers/or funders of school buildings.